Inverse Association Between Serum Vitamin B12 Concentration and Obesity Among Adults in the United States - Sun, Yangbo; Sun, Minxian; Liu, Buyun; Du, Yang; Rong, Shuang; Xu, Guifeng; Snetselaar, Linda G.; Bao, Wei (Frontiers in Endocrinology, 2019)
Introduction: Previous studies on the association of serum vitamin B12 concentrations with obesity have yielded inconsistent findings. We evaluated the cross-sectional associations of serum vitamin B12 concentrations with obesity in a nationally representative sample of U.S. adults. Methods: We included 9,075 participants aged ≥ 20 years in the National Health and Nutrition Examination Survey 2011-2014. Serum vitamin B12 concentrations were measured by electrochemiluminescence immunoassay. Obesity was defined as BMI ≥ 30 kg/m2. We used logistic regression with sample weights to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). Results: Serum vitamin B12 concentrations were lower among obese adults compared with non-obese adults. After adjustment for age, gender, race/ethnicity, socioeconomic status, dietary and lifestyle factors, use of medications that could affect the serum vitamin B12 levels, dietary supplement use and fasting time, the multivariable-adjusted ORs (95% CIs) of obesity were 1.00 (reference), 0.95 (0.79, 1.14), 0.86 (0.74, 0.99), and 0.71 (0.60, 0.84) (p for trend <0.001) for increasing quartiles of serum vitamin B12 concentrations. Conclusions: In a large nationally representative sample of U.S. adults, higher serum vitamin B12 levels were associated with lower risk of obesity. Further investigation is needed to understand the underlying mechanisms.